Big wonderful thing : a history of Texas - Harrigan, Stephen, 1948- (Austin, TX : University of Texas Press, 2019)
The story of Texas is the story of struggle and triumph in a land of extremes. It is a story of drought and flood, invasion and war, boom and bust, and the myriad peoples who, over centuries of conflict, gave rise to a place that has helped shape the identity of the United States and the destiny of the world.
Castaways -- Golden cities -- Woe to us -- The lady in blue -- Voyageurs -- God's work -- Filibusters -- God speed ye -- The Texas dream -- The consequence of failure -- Come and take it -- The Alamo is ours! -- Vengeance -- Aftermath -- Spartan spirit -- "Savage ware fare" -- The broken flagpole -- Los diablos tejanos -- The crisis of the crisis -- Robbers and lawyers -- Warriors and refugees -- I will never do it -- With throbbing hearts -- Reconstructed -- The end of Comancheria -- Fenced in -- Turn Texas loose -- Bipedal brutes -- Scorpions and horny toads -- A thousand little devils -- Gushers -- Light coming on the plains -- Sediciosos -- Pa -- War at home and abroad -- The blacksnake whip -- Music and mayhem -- The boy from the hill country -- Centennial -- Passionate ones -- Texans at war again -- The show of shows -- A new Texas -- Ye shall know the truth -- The lord takes a
"The Texas bookshelf"--Title page.
Includes bibliographical references (pages 836-890) and index.
Keywords: Texas -- History; Texas; History